A study on the effectiveness of new applications by providing up-to-date real time information guide for user of GoKL city bus / Nor Hasliny Rusli - Rusli, Nor Hasliny (2018)
Public transportation services are basic facilities provided by governments of certain countries to their citizens. With the existence of public transportation services, it may helped them to travel from one place to another conveniently. This research focuses on tourists using the ‘GoKL City Bus’ service in Kuala Lumpur City, to travel places of interest free of charge and free from unnecessary hassle. The outcome is the hoped that the government will promote tourism in a better way and at the same time it will determine the effectiveness of a new Mobile Application model that is to be introduced in near future. This research was done manually by distributing survey questionnaires to around 50 respondents. The findings of this research will be used to develop the new mobile application for tourists to easily find and locate food courts, entertainments, shopping complexes, leisure centres and other attractions nearby. Hopefully, this research will be able to improve public transportation services and tourism in Malaysia besides promoting the use of this mobile application.